FLUID BED TECHNOLOGY: OVERVIEW AND PARAMETERS FOR PROCESS SELECTION (International Journal of Pharmaceutical Sciences and Drug Research, 2018)
Formulation development is the most emerging and upcoming face of pharmaceutical technology in the current era. It is contemporarily capturing the market leaps and bounds with recent trends and developments with its innovative techniques. The day-to-day advancements in the research have provided an edge to this brilliant branch of pharmaceutical sector for not only uplifting the pharmacy profession but also to conquer the diseased state for nurturing the health and humanity. The fluid-bed technology or air-suspension process is the potential tool to develop newer trends and implications in the sector of formulation development with maximum therapeutic efficacy. The technology is used for granulation/agglomeration, layering and coating of a wide range of particle size. In addition; the technique can be used for the drying process as well. The three patterns of the fluid-bed processes could be characterized by the position/location of the spray nozzle i.e. top spray, bottom spray or tangential spray. This article reviews the three techniques with some innovative fluid bed pelletizing technologies like CPS™, MicroPx™, ProCell™ and discusses their applications, advantages and limitations. These advanced pelletizing technologies are recentely added to complement the actual capabilities of standard fluid bed processing for development of various dosage forms of “Multiple Unit Particulate Systems” (MUPS) with better therapeutic efficacy and economic benefits.